ON THE SPECIFIC CHARACTERISTICS OF TEACHING UZBEK AND PUPILS OF OTHER NATIONALITIES IN THE RUSSIAN LANGUAGE - Xodjiyev R. M. (Zeta Repository, 2023)
This article discusses the role, status and significance of studying the Russian language in the professional activities of pupils in groups of non-linguistic areas of education in higher educational institutions. The author examines the existing differences between the Uzbek and Russian languages and makes some suggestions to overcome the difficulties that arise. The article may be interesting and useful for teachers of the Russian language in higher and secondary educational institutions.